2014
DOI: 10.3402/ijch.v73.23540
|View full text |Cite
|
Sign up to set email alerts
|

Neurosensory sequelae assessed by thermal and vibrotactile perception thresholds after local cold injury

Abstract: BackgroundLocal freezing cold injuries are common in the north and sequelae to cold injury can persist many years. Quantitative sensory testing (QST) can be used to assess neurosensory symptoms but has previously not been used on cold injury patients.ObjectiveTo evaluate neurosensory sequelae after local freezing cold injury by thermal and vibrotactile perception thresholds and by symptom descriptions.DesignFifteen patients with a local freezing cold injury in the hands or feet, acquired during military traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 13 publications
4
20
0
1
Order By: Relevance
“…There is however congruence between QST findings and subjective symptom descriptions in this study, which supports the idea that our QST findings are of clinical value. In a previous study, we observed a similar QST pattern among military conscripts who suffered from cold injuries and were enrolled in the same type of training as the current study population (8).…”
Section: Quantitative Sensory Testingmentioning
confidence: 73%
See 4 more Smart Citations
“…There is however congruence between QST findings and subjective symptom descriptions in this study, which supports the idea that our QST findings are of clinical value. In a previous study, we observed a similar QST pattern among military conscripts who suffered from cold injuries and were enrolled in the same type of training as the current study population (8).…”
Section: Quantitative Sensory Testingmentioning
confidence: 73%
“…This has been shown among cold injury victims (8) and since our subjects are exposed to similar repeated tissue cooling and local ischemia (10) similar symptoms could be expected.…”
mentioning
confidence: 75%
See 3 more Smart Citations